Burnout syndrome and its determinants among healthcare workers during the first wave of the Covid-19 outbreak in Italy: a cross-sectional study to identify sex-related differences: Burnout and sex-related differences in healthcare workers - Brera, Alice Silvia; Arrigoni, Cristina; Dellafiore, Federica; Odone, Anna; Magon, Arianna; Nania, Tiziana; Pittella, Francesco; Palamenghi, Lorenzo; Barello, Serena; Caruso, Rosario (La Medicina del Lavoro, 2021)
Introduction: Several studies described burnout levels of healthcare workers (HCWs) during the COVID-19 pandemic; however, sex-related differences remain poorly investigated. Objective: To describe sex-related differences in burnout and its determinants among HCWs during the first pandemic wave of the COVID-19 in Italy. Methods: A cross-sectional study was performed between April and May 2020. The framework given by the Job Demands Resources (JD-R) model was used to assess burnout determinants (risk and protective factors). Results: Male HCWs (n=133) had higher levels of depersonalization than female HCWs (P=0,017) and female HCWs (n=399) reported greater emotional exhaustion rates (P=0,005). Female nurses were the most exposed to burnout (OR=2,47; 95%CI=1,33-4,60; P=0,004), emotional exhaustion (OR=1,89; 95% CI=1,03-3,48; P=0,041), and depersonalization (OR=1,91; 95% CI=1,03-3,53; P=0,039). Determinants of burnout differed between sexes, and some paradoxical associations were detected: the score of job demands was a protective factor in females for burnout, emotional exhaustion, and depersonalization, resilience was a risk factor for males. Conclusions: This study reveals that the stressors in male and female HCWs tended to be associated with burnout differently. Both sexes showed alarming burnout levels, even if the weights of emotional exhaustion and depersonalization acted in different ways between the sexes. The revealed paradoxical effects in this study could reflect the study’s cross-sectional nature, highlighting that more resilient and empathic individuals were more consciously overwhelmed by the challenges related to the COVID-19 pandemic, thus reporting higher scores of emotional exhaustion and burnout. Future in-depth and longitudinal analyses are recommended to further explore sex-related differences in burnout among HCWs.